ECONOMIC CULTURAL AND POLITICAL FUNDAMENTALS OF THE FORMATION OF THE FIRST STATES IN SOUTHERN UZBEKISTAN - TURSUNOV SAYPULLA NARZULLAEVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
The idea behind this article focuses on the controversial history of the medieval Chaghaniyan state in the Surkhandarya oasis. Thanks to the Uzbek statehood, it is important to arouse the interest of the current generation in the history of the country on the basis of the study of customs, traditions, values and socioeconomic development.